Indigenous Fungi as Controllers of Fruit Rot Disease in Organic and Inorganic Cocoa Plants - Ratnawati, Ratnawati; Arfan, Arfan; Hayati, Nahdhatul; Jaya, Kasman (Devotion : Journal of Research and Community Service, 2026)
Exploration of endophytic fungi originating from the rhizosphere of organic and inorganic cocoa plants has the potential to be used as a control for fruit rot caused by Phytopthora palmivora. The use of these fungi can reduce the negative impact caused by the use of certain chemicals in maintaining yields affected by plant pests. This study aims to identify endophytic fungi in the rhizosphere of organic cocoa plantations in Palolo Village and inorganic plantations in Sidondo Village and to test the inhibitory power of the endophytic fungi obtained as a control for cocoa fruit rot disease. This research consists of two stages: Stage I, exploration of endophytic fungi, and Stage II, selection of endophytic fungi from the cocoa rhizosphere (in vitro test). The research results identified several endophytic fungi originating from the rhizosphere of inorganic cocoa, namely isolates SAO1; Gliocladium sp., SAO2; Aspergillus niger mf-1, SAO3; Aspergillus niger mf-2, and SAO4; Trichoderma sp. From organic cocoa fields, the following isolates were found: NO1 (Gliocladium sp. mf-1); NO2 (Aspergillus niger mf-1); NO3 (Gliocladium sp. mf-2); NO4 (Aspergillus terreus); NO5 (Trichoderma sp); NO6 (Aspergillus niger mf-2). Isolates from both organic cocoa fields, namely isolate NO5, and inorganic fields, namely isolate SAO4, were able to inhibit the growth of the pathogen P. palmivora with an inhibition rate of up to 70% through a type of mechanism involving competition for space and the release of volatile exudates that were able to inhibit the pathogen.